YouTube advertising appeals on generation Z’s purchase intention of beauty products: a predictive approach - Chan, Tak Jie; Somasundram, Kirttine; Tian, Yang; Adzharuddin, Nor Azura; Hashim, Nor Hazlina (Cogent OA, 2025)
The study investigates Generation Z’s purchase intentions in the beauty industry that are impacted by YouTube advertising appeals. A structured questionnaire and a quantitative approach were used to collect data from a total of 205 respondents who belonged to Generation Z. The study examined the impact of five types of advertising appeals, namely emotional, rational, aesthetic, celebrity endorsement, and inclusivity on purchase intention. The study utilized Aristotle’s Rhetorical Theory as the underpinning theoretical framework. Results from Partial Least Square Structural Equation Modeling (PLS-SEM) revealed that emotional appeal and celebrity endorsement significantly predicted purchase intention among Generation Z consumers, while rational, aesthetic, and inclusivity appeals did not. These findings underscore the effectiveness of emotional and celebrity endorsement appeals in YouTube advertising strategies targeting Generation Z within the beauty sector. The study contributes to both theoretical and practical implications for marketers aiming to enhance digital advertising strategies tailored to Generation Z’s unique consumer behaviors.